2020
DOI: 10.3847/1538-4365/ab6216
|View full text |Cite
|
Sign up to set email alerts
|

CME–CME Interactions as Sources of CME Geoeffectiveness: The Formation of the Complex Ejecta and Intense Geomagnetic Storm in 2017 Early September

Abstract: Coronal mass ejections (CMEs) are the primary sources of intense disturbances at Earth, where their geo-effectiveness is largely determined by their dynamic pressure and internal magnetic field, which can be significantly altered during interactions with other CMEs in interplanetary space. We analyse three successive CMEs that erupted from the Sun during September 4-6, 2017, investigating the role of CME-CME interactions as source of the associated intense geomagnetic storm (Dst min = −142 nT on September 7). … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(86 citation statements)
references
References 126 publications
0
86
0
Order By: Relevance
“…The intrinsic flux rope properties can give early warning of the potential space weather consequences, but most importantly it provides critical information for constraining flux ropes in a variety of semiempirical and first-principle models describing the propagation and evolution of CMEs in the corona and heliosphere, such as ForeCAT and FIDO (Kay et al, 2013(Kay et al, , 2017, 3DCORE (Möstl et al, 2018), INFROS (Sarkar et al, 2020), Enlil (Odstrcil et al, 2004), EUropean Heliospheric FORecasting Information Asset (EUHFORIA; Pomoell and Poedts, 2018), and SUSANOO-CME (Shiota and Kataoka, 2016). Although first-principle models are so-far routinely run with only cone-model CMEs for space weather forecasting purposes, for example EUHFORIA is now actively tested with magnetized CMEs to give improved predictions and more realistic information on the effect of CME interactions (Scolini et al, 2019(Scolini et al, , 2020Verbeke et al, 2019). The intrinsic magnetic field structure of a CME flux rope can be estimated using indirect observational proxies that combine characteristics of structures in the solar atmosphere related to the erupting CME, such as filament details, flare ribbons, and sigmoids (e.g., Palmerio et al, 2017Palmerio et al, , 2018Gopalswamy et al, 2018, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic flux rope properties can give early warning of the potential space weather consequences, but most importantly it provides critical information for constraining flux ropes in a variety of semiempirical and first-principle models describing the propagation and evolution of CMEs in the corona and heliosphere, such as ForeCAT and FIDO (Kay et al, 2013(Kay et al, , 2017, 3DCORE (Möstl et al, 2018), INFROS (Sarkar et al, 2020), Enlil (Odstrcil et al, 2004), EUropean Heliospheric FORecasting Information Asset (EUHFORIA; Pomoell and Poedts, 2018), and SUSANOO-CME (Shiota and Kataoka, 2016). Although first-principle models are so-far routinely run with only cone-model CMEs for space weather forecasting purposes, for example EUHFORIA is now actively tested with magnetized CMEs to give improved predictions and more realistic information on the effect of CME interactions (Scolini et al, 2019(Scolini et al, , 2020Verbeke et al, 2019). The intrinsic magnetic field structure of a CME flux rope can be estimated using indirect observational proxies that combine characteristics of structures in the solar atmosphere related to the erupting CME, such as filament details, flare ribbons, and sigmoids (e.g., Palmerio et al, 2017Palmerio et al, , 2018Gopalswamy et al, 2018, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is entirely possible that ICME2 had a shock before reaching ACE, since the upstream conditions were different. In that context, this shock may have propagated through ICME1 and may even have merged with the shock in front of ICME1 (see Lugaz et al 2005;Scolini et al 2020b, for more details on shock magnetic cloud interactions).…”
Section: Observations At L1 and Geoeffectivitymentioning
confidence: 99%
“…It was shown that interacting CMEs in the heliosphere amplify the geomagnetic response (Scolini et al, 2020). This amplification could be due to shock compression inside interplanetary CMEs (ICMEs) (see e.g., Shen et al, 2018;Xu et al, 2019), due to the generation of high energy protons (see e.g., Joshi et al, 2013) or due to the heights above the photosphere at which the shocks are formed (see e.g., Gopalswamy et al, 2013).…”
Section: Geoeffectiveness Of Cmesmentioning
confidence: 99%